Excess weight in children living in rural areas related to the nutritional profile and to maternal habits - Erika Barbosa Lagares (Investigación y Educación en Enfermería, 2021)
Objective To assess the relationship between the nutritional status and eating habits of children aged from five to ten years old and their mothers, living in rural areas.Methods A cross-sectional study conducted with 156 children aged from five to ten years old, registered in the Family Health Strategies of the rural area of the Municipality of Divinópolis-MG (Brazil) from July 2017 to April 2018.Results The prevalence of excess weight was 27.5%. The following parameters were significantly associated with excess weight in the children: maternal waist circumference (OR=1.04), protein consumption (OR=1.02), irregular consumption of natural juice (OR=5.05), and the most favored socioeconomic level, C1 social stratum (OR=3.54). Regarding the correlation between nutrient intake of the children and their mothers, most of the correlations were weak to moderate, being statistically significant for all the dietary components evaluated (r=0.185 to 0.496).Conclusion Maternal nutritional status was related to the child's excess weight and a weak to moderate correlation was observed for nutrient intake among the children and their mothers. A high prevalence of children with excess weight was observed in the rural areas. The results point to the need to implement collective approaches, targeted at rural families, so as to prevent this problem.